Initial low‐dose oral levothyroxine in a child with Down syndrome, myxedema, and cardiogenic shock - Annika Janson; Cathrin Hällström; Magnus Iversen; Mikael Finder; Amira Elimam; Ricard Nergårdh (Clinical Case Reports, 2019)
Abstract Myxedema is extremely rare in children, and guidelines are lacking. We treated a 12‐year‐old girl with myxedema and cardiogenic shock with initial low dose (0.3‐2.5 μg/kg body weight/day) of oral levothyroxine and intensive care. Oral administration may safely revert children's myxedema in a dosage resembling that for hypothyroidism.